Entrepreneurship Training and Self-Employment among University Graduates : Evidence from a Randomized Trial In Tunisia - Premand, Patrick (World Bank, Washington, DC, 2013)
In economies characterized by low labor demand and high rates of youth unemployment, entrepreneurship training has the potential to enable youth to gain skills and create their own jobs. This paper presents experimental evidence on a new entrepreneurship track that provides business training and personalized coaching to university students in Tunisia. Undergraduates in the final year of licence appliquee were given the opportunity to graduate with a business plan instead of following the standard curriculum. This paper relies on randomized assignment of the entrepreneurship track to identify impacts on labor market outcomes one year after graduation. The analysis finds that the entrepreneurship track was effective in increasing self-employment among applicants, but that the effects are small in absolute terms. In addition, the employment rate among participants remains unchanged, pointing to a partial substitution from wage employment to self-employment. The evidence shows that the program fostered business skills, expanded networks, and affected a range of behavioral skills. Participation in the entrepreneurship track also heightened graduates optimism toward the future shortly after the Tunisian revolution.